2010
DOI: 10.1159/000316445
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Incomplete Insertion of Electrodes in Cochlear Implant Surgery: A Histopathologic Study

Abstract: Objectives: Atraumatic and complete insertion of the electrode array is a stated objective of cochlear implant surgery. However, it is known that obstructions within the cochlea such as new bone formation, cochlear otosclerosis, temporal bone fracture, and cochlear anomalies may limit the depth of insertion of the electrode array. In addition, even among patients without obvious clinical or radiographic indicators of obstruction, incomplete insertion may occur. The current study is a histopathologic evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
1
31
1
2
Order By: Relevance
“…The serial sections of the temporal bones were reconstructed, and the numbers of spiral ganglion cells in Rosenthal’s canal were calculated by conventional 2-D methods (Guild, 1921; Schuknecht, 1993). The most apical section of the cochlea containing the electrode tip in which there was histologic evidence, such as fibrous sheath around the electrode (Li et al, 2007; Lee et al, 2011), and the entry point into the cochlea were determined. The electrode length within the cochlea and the electrode length located in the scala media/vestibuli or spiral ligament were also determined using the 2-D reconstructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serial sections of the temporal bones were reconstructed, and the numbers of spiral ganglion cells in Rosenthal’s canal were calculated by conventional 2-D methods (Guild, 1921; Schuknecht, 1993). The most apical section of the cochlea containing the electrode tip in which there was histologic evidence, such as fibrous sheath around the electrode (Li et al, 2007; Lee et al, 2011), and the entry point into the cochlea were determined. The electrode length within the cochlea and the electrode length located in the scala media/vestibuli or spiral ligament were also determined using the 2-D reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of electrode insertional trauma was assessed by adapting a method previously described (Li et al, 2007; Lee et al, 2011) and presented in Table 2. Damage to the osseous spiral lamina, lateral cochlear wall and basilar membrane was used as markers for insertional trauma.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that full insertions of any CI electrode are not always achieved, particularly by inexperienced surgeons, and that this is often (although not always) due to obstructive pathology (Lee et al 2010). Published reports of surgical experiences with the MED-EL electrode arrays suggest that full insertion is achieved in the majority of cases of apparently patent cochleae.…”
Section: Surgical Considerations and Insertion Traumamentioning
confidence: 99%
“…Furthermore, it is possible that more shallow insertions may be associated with pre-existing obstructive pathology or insertion trauma (Neumann et al 2005;Lee et al 2010), further complicating interpretation. Skinner et al (2002), however, reported a positive correlation between word recognition and insertion depth (ranging from 11.9 to 25.9 mm) in 26 users of the Nucleus 22 device.…”
Section: The Effects Of Insertion Depth On Speech Recognition With Shmentioning
confidence: 99%
“…In contemporary surgical technique, it is often difficult to achieve electrode insertion deeper than the first basal turn even if the cochlea is anatomically normal (Lee et al, 2011). Incomplete insertion may create a mismatch between cochlear place and frequency.…”
Section: Introductionmentioning
confidence: 99%